2018
DOI: 10.1002/eco.2011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of rainfall partitioning by a deciduous shrub using a variable parameters Gash model

Abstract: Alpine deciduous shrubs play an important role in local water cycle for ecosystems of Qinghai‐Tibet Plateau, but rainfall partitioning of the deciduous shrubs has not been fully understood due to significant variation in spatial coverage and leaf storage capacity, especially the lack of appropriate model to describe relevant processes. To assess these processes, field experiments were performed to determine vegetation and atmospheric parameters for the deciduous Potentilla fruticosa shrub in the growing season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This indicates that LAI was capable of reflecting the dynamics of S rather than I , with a dominant component of wet evaporation during the growing season. The results of this study therefore suggested that LAI was a more effective canopy parameter than C in terms of mirroring the dynamics of S , owing largely in part to the convenience with which it could be measured; and it was also closely associated with bio‐physical processes in the canopy, such as leaf growth and water retention (Deguchi et al, 2006; Návar, 2019a; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This indicates that LAI was capable of reflecting the dynamics of S rather than I , with a dominant component of wet evaporation during the growing season. The results of this study therefore suggested that LAI was a more effective canopy parameter than C in terms of mirroring the dynamics of S , owing largely in part to the convenience with which it could be measured; and it was also closely associated with bio‐physical processes in the canopy, such as leaf growth and water retention (Deguchi et al, 2006; Návar, 2019a; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…For the Wang model, the simulated I error was relatively low for small rain events because of a lower proportion of wet evaporation to I ; however, it would be risky to employ a constant rate to quantify wet evaporation for heavy rain events (>25 mm), as this could lead to large errors based on the higher proportion of I . Therefore, our results suggest that when the two models are applied, it would be more effective to adopt event‐based and changeable meteorological parameters, such as wet evaporation rate, considering the amount and duration of the rain events (e.g., Návar, 2019b; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations